Assessing the Culture of Engagement on a University Campus - Nancy Franz; Jeri Childers; Nicole Sanderlin (The University of Alabama, 2022)
This article describes one team's efforts to assess the culture of engagement at Virginia Tech. The team utilized a two-pronged approach to analyze the current culture of engagement on campus. This included focus groups with faculty, administrators, and graduate students in two colleges at the university to address pedagogy, implications, and practical issues related to engagement. Analysis of college strategic plans was also completed to assess language related to engagement and engaged scholarship. We found why faculty, administrators, and students conduct engagement work and the challenges and opportunities of doing so. We also discovered what criteria these individuals use to determine quality engagement, what they believe engagement on campus should look like, and the products derived from engagement work. This article describes our team's efforts and documents the lessons learned to inform similar efforts on other campuses.